The philosophy of communication in technology-based education: Study of research trends in the last three years assisted by NVivo 12 Pro - Geofakta Razali (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
Communication as part of science will always be associated with philosophical studies which have three criteria, such as aspects of ontology, epistemology, and axiology. Some research studies that make communication the subject of discussion are very abundant in Indonesia, especially when aligned with the use of technology that accompanies it. Studies on communication science are also part of learning activities, starting from the level of early childhood education up to the tertiary level. Communication skills or abilities are needed in the learning process. This research aims to find patterns or trends in communication research in learning activities accompanied by the application of technology based on studies of the philosophy of communication. Literature was obtained through search with the assistance of PoP with a range of 2021-2023. The analysis was conducted with the assistance of NVivo 12 Pro after going through data reduction using the Prisma method. It eased to find connections between literature groups and the characteristics of the literature obtained. Each piece of literature reviewed was coded such as year, serial number, type of education, level of education or age, and the technology used. The results obtained based on an analysis of 20 kinds of literature showed that research studies on communication science in collaboration with other fields through the use of technology are starting to get a lot of attention, as can be seen from research that is dominated by 2023, where the era of globalization can no longer be dammed, but must be faced and implemented to achieve meaningful knowledge for life, especially through learning activities. The research trend of communication science in the field of education that applies technology, when viewed from the aspect of philosophy, is dominantly in the ontology group. This is followed by the epistemology category, and the least is the axiology category.